2022
DOI: 10.1096/fj.202101637r
|View full text |Cite
|
Sign up to set email alerts
|

The dual role of dopamine in the modulation of information processing in the prefrontal cortex underlying social behavior

Abstract: Dopamine in the prefrontal cortex is essential for the regulation of social behavior. However, stress‐causing social withdrawal also promotes dopamine release in the prefrontal cortex. Thus, this evidence suggests opposite functions of dopamine in the prefrontal cortex. However, the influence of dopamine on prefrontal functions is yet to be fully understood. Here, we show that dopamine differentially modulated the neuronal activity triggered by social stimuli in the prefrontal cortex, depending on the duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 64 publications
2
10
0
Order By: Relevance
“…It is believed that dopamine neural activity in the resting state results in sustained dopamine release (tonic release) (Grace, 1991). In agreement, I have previously shown that alterations of the mean firing rate of VTA dopamine neurons (under anaesthetized conditions) by chemogenetics are consistent with changes in dopamine levels in the prefrontal cortices of awake EGF‐treated rats and normal rats in the resting state (Sotoyama et al, 2021, 2022). On the other hand, I reported previously that there was no significant difference in the spike within the burst (SWB), which is a burst firing index, of VTA dopamine neurons between controls and EGF‐treated rats under anaesthetized conditions (Sotoyama et al, 2021).…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…It is believed that dopamine neural activity in the resting state results in sustained dopamine release (tonic release) (Grace, 1991). In agreement, I have previously shown that alterations of the mean firing rate of VTA dopamine neurons (under anaesthetized conditions) by chemogenetics are consistent with changes in dopamine levels in the prefrontal cortices of awake EGF‐treated rats and normal rats in the resting state (Sotoyama et al, 2021, 2022). On the other hand, I reported previously that there was no significant difference in the spike within the burst (SWB), which is a burst firing index, of VTA dopamine neurons between controls and EGF‐treated rats under anaesthetized conditions (Sotoyama et al, 2021).…”
Section: Resultssupporting
confidence: 77%
“…For the chronic treatment, the CNO solution was filled in a mini‐osmotic pump (Alzet model 2002, Durect Co., CA, USA), and then the mini‐osmotic pump was implanted under the skin. The dose of CNO was determined according to our previous study (Sotoyama et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This serotoninergic duality in social sensitivity seems to occur in concert with other neurochemical systems, such as the opioid system ( Refs 197,198). Similarly, other studies have pointed out the importance of dopaminergic pathways in social support/positive social environments, which state that the level of dopaminergic system activity could influence social support via the capacity of cognitive function ( Refs 199,200). Nonetheless, further research trying to decipher the role of each neural pathway on the effects of social support/positive social environments, especially in the context of immunosenescence, should be addressed.…”
mentioning
confidence: 92%